Penerapan Sistem Informasi Surat Keterangan Pendamping Ijazah STMIK Kaputama Secara Online - Fauzie, Achmad; Syahputra, Siswan; Ferdillah, Tengku Didi; Restuono, Langgeng (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
Many STMIK Kaputama academic information systems have been implemented for students, starting with the Academic information system, STMIK Kaputama online information system, library information system, financial information system, and other information systems. STMIK Kaputama does not yet have a Diploma Information System, or SKPI, as it is often called, although according to the Ministry's regulations, SKPI must be issued in Indonesia's public and private universities with the aim of helping graduates find jobs that match their qualifications. . That is why STMIK Kaputama has built an online information system on the Diploma Companion Certificate, the flow of which is structured according to learning achievements and validates files according to the competencies proposed by students. The existence of the SKPI electronic information system means that STMIK Kaputama developed the system and complied with the rules established by the ministry.